2015
DOI: 10.1017/s1751731115000798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of faecal soiling on skatole and androstenone occurrence in organic entire male pigs

Abstract: Production of entire male pigs could be a future strategy for organic pig production. However, production of entire males leads to increased risk of carcasses with elevated boar taint levels. It is hypothesized that skatole levels in pig meat are affected by faecal soiling and that organic housing facilities can increase the risk of pigs being heavily soiled. Therefore, the overall aim of this study was to investigate if increased pig and pen soiling increases skatole concentration in entire male pigs. In five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…While skatole levels are typically elevated in intact males, they are also detectable in barrows and gilts, albeit in smaller quantities [20]. Furthermore, the absorption of skatole can occur through the skin via contact with feces or through the respiratory system via inhalation, which may vary depending on environmental conditions and housing facilities [78]. Regarding androstenone, the results were quite heterogeneous, and the presence of androstenone was not detected in some animals, regardless of the group.…”
Section: Discussionmentioning
confidence: 98%
“…While skatole levels are typically elevated in intact males, they are also detectable in barrows and gilts, albeit in smaller quantities [20]. Furthermore, the absorption of skatole can occur through the skin via contact with feces or through the respiratory system via inhalation, which may vary depending on environmental conditions and housing facilities [78]. Regarding androstenone, the results were quite heterogeneous, and the presence of androstenone was not detected in some animals, regardless of the group.…”
Section: Discussionmentioning
confidence: 98%
“…Sachant que le scatol peut être absorbé au niveau pulmonaire comme cela a été démontré chez le lapin (Bray et Carlson, 1980), ce phénomène pourrait contribuer à augmenter la teneur en scatol du tissu adipeux quand il fait chaud. Indépendamment de la saison, plusieurs études montrent que la concentration en scatol du gras est plus forte chez les animaux élevés en loges sales (Hansen et al, 1994 ;Thomsen et al, 2015a ;Parois et al, 2017b). Ceci peut s'expliquer comme précédemment par une augmentation de l'absorption au niveau des poumons et/ou au travers de la peau, en particulier celle du ventre du fait de sa plus grande finesse.…”
Section: L'environnement Physiqueunclassified
“…Housing system This study is part of a larger study on organic entire male pigs, with a thorough description of housing system and study design to be found in Thomsen et al (2014a and2014b). The pigs were reared according to the standard Danish organic production system, with an indoor area consisting of an activity area with solid and partially slatted floors and a resting area with straw bedding.…”
Section: Animalsmentioning
confidence: 99%